2017
DOI: 10.1002/ps.4778
|View full text |Cite
|
Sign up to set email alerts
|

Increased chalcone synthase (CHS) expression is associated with dicamba resistance in Kochia scoparia

Abstract: Prior work has shown that the flavonols quertecin and kaemperfol compete with auxin for intercellular movement and vascular loading via ATP-binding cassette subfamily B (ABCB) membrane transporters. The results of this study support a model in which constitutively increased CHS expression in the meristem produces more flavonols that would compete with dicamba for intercellular transport by ABCB transporters, resulting in reduced dicamba translocation. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…Previous research found that auxinic herbicide resistance in wild mustard ( Sinapis arvensis ), false cleavers ( Galium spurium ), kochia ( Kochia scoparia ), and yellow starthistle ( Centaurea solstitialis ) was not attributable to differences in herbicide absorption, translocation and/or metabolism and, by deduction, might be attributable to other mechanisms, such as altered target site. A different dicamba‐resistant K. scoparia population was found to have reduced dicamba translocation …”
Section: Discussionsupporting
confidence: 60%
“…Previous research found that auxinic herbicide resistance in wild mustard ( Sinapis arvensis ), false cleavers ( Galium spurium ), kochia ( Kochia scoparia ), and yellow starthistle ( Centaurea solstitialis ) was not attributable to differences in herbicide absorption, translocation and/or metabolism and, by deduction, might be attributable to other mechanisms, such as altered target site. A different dicamba‐resistant K. scoparia population was found to have reduced dicamba translocation …”
Section: Discussionsupporting
confidence: 60%
“…This transport can be further regulated by the function of additional interacting proteins and by flavonoids, which modulate the activity of ABCB transporters (12). In two recent reports, reduced translocation of auxins has been shown to be associated with resistance (13,14). Furthermore, this reduction in auxin transport was recently associated with chalcone synthase up-regulation in the same kochia line used in this study (14).…”
Section: Significancementioning
confidence: 54%
“…Although we found some effects on expression of genes of the flavonoid pathway, it is doubtful that inhibition of this pathway would result in phytotoxicity, especially since Böger reported that a compound ( R ‐metolachlor) that inhibits chalcone synthase is not phytotoxic. However, chalcone synthase has been reported to be involved in more than synthesis of t ‐chalcone, as upregulation of the chalcone synthase gene is associated with resistance to the herbicide dicamba, a benzoic acid analog herbicide . Nguyen et al reported t ‐chalcone to be a weak inhibitor of phosphoenolpyruvate carboxylase (PEPC), with increasing activity upon hydroxylation of either or both rings of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…However, chalcone synthase has been reported to be involved in more than synthesis of t-chalcone, as upregulation of the chalcone synthase gene is associated with resistance to the herbicide dicamba, a benzoic acid analog herbicide. 55 Nguyen et al 56 reported t-chalcone to be a weak inhibitor of phosphoenolpyruvate carboxylase (PEPC), with increasing activity upon hydroxylation of either or both rings of the molecule. PEPC from C 4 plants was more sensitive than that from C 3 plants.…”
Section: Discussionmentioning
confidence: 99%